2012
DOI: 10.3758/s13420-012-0089-z
|View full text |Cite
|
Sign up to set email alerts
|

Overshadowing and associability change: Examining the contribution of differential stimulus exposure

Abstract: In two appetitive conditioning experiments with rats, we investigated the mechanisms responsible for demonstrations of the superior associability of overshadowed conditioned stimuli (CSs) relative to control CSs. In Experiment 1, we investigated whether previous demonstrations were a consequence of differences in the relationship between the CSs and the unconditioned stimulus (US) or of differences in the conditions of exposure to the CSs. Rats received trials with X, Y, and an AB compound, but no delivery of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
5
1
Order By: Relevance
“…We proposed that this was due to differences in the conditions of exposure (in compound or in isolation), and tested this prediction by using an overshadowing procedure that equated these conditions. In this case, we observed the opposite of our initial result—lower associability for the overshadowed cue than for a control cue that had higher associative strength (Jones & Haselgrove, 2013). The parallels between this series of experiments and the present examination of associability changes during blocking are obvious.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…We proposed that this was due to differences in the conditions of exposure (in compound or in isolation), and tested this prediction by using an overshadowing procedure that equated these conditions. In this case, we observed the opposite of our initial result—lower associability for the overshadowed cue than for a control cue that had higher associative strength (Jones & Haselgrove, 2013). The parallels between this series of experiments and the present examination of associability changes during blocking are obvious.…”
Section: Discussioncontrasting
confidence: 96%
“…Like the present Experiment 1, this was a surprising result that did not initially seem to be compatible with Mackintosh's (1975a) model of learning. Further examination, however, revealed that a similar effect could be produced by presenting the stimuli according to the same schedule in the absence of reinforcement (Jones & Haselgrove, 2013). We proposed that this was due to differences in the conditions of exposure (in compound or in isolation), and tested this prediction by using an overshadowing procedure that equated these conditions.…”
Section: Discussionmentioning
confidence: 98%
“…Cues that are presented without any consequences appear to lose associability when they are later paired with a meaningful outcome (the latent inhibition effect; see Holmes & Harris, 2010, for a review). It is possible that this process still occurs even when cues are presented with reliable consequences (e.g., Jones & Haselgrove, 2013; Kaye & Pearce, 1984). Latent inhibition effects have been notoriously difficult to demonstrate in humans (see Byrom et al, 2018), but if they were to have a substantial impact on cue associability in this type of explicit learning task, then they could contribute to greater attention being paid to the rarer of two predictive cues.…”
Section: Discussionmentioning
confidence: 99%
“…Cues that are presented without any consequences appear to lose associability when they are later paired with a meaningful outcome (the latent inhibition effect, seeHolmes & Harris, 2010 for a review). It is possible that this process still occurs even when cues are presented with reliable consequences (e.g Jones & Haselgrove, 2013;.…”
mentioning
confidence: 99%
“…This effect has subsequently been reported in a diverse range of species including rats (e.g., Bonardi, 1991;Dopson, Pearce, Haselgrove, 2009;Jones & Haselgrove, 2013, Mackintosh, 1975, mice (Sanderson, Jones & Austen, 2016), snails (Prados et al, 2013), honeybees (Cheng & Spetch, 2001;Guerrieri, Lachit, Gerber & Giurfa, 2005) and humans (Crookes & Moran, 2003;Dickinson, Shanks & Eveden, 1984;Le Pelley, Oakeshott, McLaren, 2005), and a variety of theoretical accounts have been provided in order to account for its ubiquitous nature. According to the performance-deficit account an association is formed between the US and the additional element of the compound (X), but the expression of this association (X -US) is prevented during a testing phase (e.g., Acrediano, Escobar & Miller, 2004;Denniston, Savastano & Miller, 2001;Miller & Matzel, 1988).…”
mentioning
confidence: 94%